EFFECT OF LEADER MEMBER EXCHANGE, ORGANIZATIONAL CULTURE AND EMPLOYEE ENGAGEMENT ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR (CASE STUDY GEN Y IN PERUM LPPNPI) - Mahmudi, Budi; Farida Elmi (Dinasti Publisher, 2020)
This study aims to determine the effect of the leader member exchange, organizational culture, employee engagement on organizational citizenship behavior. This type of research is descriptive verification method. The population of all employees of Perum LPPNPI, decision-probability sampling technique with a sample of 200 employees. Data Analysis Structural Equation Modeling (SEM) method Partial Least Square (PLS) with 6.0 WarpPLS program. The results showed that the leader member exchange have a significant effect on employee engagement, organizational culture have a significant effect on employee engagement, employee engagement significantly influence the organizational citizenship behavior, leader member exchange have a significant effect on organizational citizenship behavior, and organizational culture significant effect on organizational citizenship behavior.